NEGOTIATING PROFESSIONAL IDENTITY: A CASE STUDY OF CULTURAL LEARNING OF ENGLISH TEACHERS AT MTS NAHDLATUT THALIBIN - Mochlis Ekowijayanto; Ibnu Syarofi; Muhammad Faiz; Nunung Sanjaya; Ahmad Dani (Jurnal Bahasa Lingua Scientia, 2025)
This research aims to explore the negotiation process of the professional identity of English teachers at MTs Nahdlatut Thalibin, a pesantren based madrasah that prioritizes local religious and cultural values. This study identifies how English teachers negotiate their roles amid the demands of a national curriculum based on global competencies and local values upheld in madrasas. Through a qualitative approach with in-depth interviews, observations, and documentation, three main themes were found: (1) teachers' perception of their professional identity, (2) adaptation strategies in learning, and (3) challenges faced in negotiating professional identity. The results of the study show that teachers at MTs Nahdlatut Thalibin view their identity as more than just language teaching, but also as cultural agents who must transfer local religious and cultural values. Strategies used by teachers include the selection of teaching materials that are sensitive to local culture, the insertion of religious values in English learning, and the translation of foreign terms using local cultural analogies. However, the main challenge facing teachers is the tension between the demand to teach English based on a global curriculum and the need to maintain local religious and cultural values. This research provides insight into how English teachers in faith-based madrassas negotiate their identities and demonstrates the importance of developing a curriculum that is sensitive to local and religious contexts in language learning.